PENGARUH PUPUK BIO-URIN DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI RUMPUT Panicum maximum - Ni Made Sastriyani Wiendra; N.N. Candraasih Kusumawati (Udayana University)
A field experiment has been conducted at Pesinggahan up-land regency of Klungkung Bali, to know the interaction effect between planted space and bio-urine dosage on the optimal production of Panicum maximum. Randomized Completely Block Design was arranged in factorial model. The planted space (J) treatments were: J1 = 10 cm • 20 cm, J2 = 20 cm • 20 cm, and J3 = 40 cm • 20 cm, and the bio-urine (B) treatments were: B0 = without bio-urine, B1 = 3,750 l ha-1 (1.44 l plot-1), B2 = 7,500 l ha-1 (2.88 l plot -1), B3 = 11,250 l ha-1 (4.32 l plot -1) and each treatment replicated three times. Result of these experiment showed that a significant interaction (P<0.05) between bio-urine fertilizer and planted space on dry weight leaf and dry weight of total forage in the second regrowth. The highest yield of dry weight forage was on the bio-urine 7,500 l ha-1 (B2) dosage and 10 cm • 20 cm (J2) space of planting. The optimal dosage was on 8,007.9 l ha-1 with 15,05 ton ha-1 maximal production.